Civilizational Narrative and Philosophy at Higher Education Institutions - N. V. Kuznetsov; A. M. Sokolov (Moscow Polytechnic University, 2021)
The authors proceed from the postulate that philosophical thinking is the highest form of human activity, integrating all other types of human activity as its elements. Hence, any occupation of a person can be understood in the authenticity of its content only in the horizon of philosophical thought. This is what the philosophical education of specialists should be focused on, regardless of the direction of their activities. The article analyzes the decisive role of philosophical thought in the formation of self-consciousness of bourgeois society. The authors argue that its success was predetermined by the development of new forms of communication that contributed to the discovery of a new dimension of human existence, involving new types of its development. The displacement of philosophy to the periphery of spiritual production indicates the extinction of creative initiative among the bourgeoisie. In conclusion, the authors turn to the experience of Soviet education as an attempt to further develop the civilizational narrative of European civilization, considering the reasons for its successes and failures. According to the authors, on the one hand, the presence of philosophy as a mandatory element of the higher education system in the USSR testified to the creative potential of the new civilizational initiative; on the other hand, this philosophy has not reached a sufficient degree of maturity to correspond to the level of Soviet society development.